ENERGY RETURN ON ENERGY INVESTMENT (EROEI) ANALYSIS OF COFIRING COAL WITH SOLID WASTE BIOMASS - Megah Bremanda Sembiring, Jen
The implementation of cofiring in Coal-Fired Power Plants (CFPP) is often considered beneficial from an environmental perspective because a portion of the coal demand is replaced by biomass, which is a clean energy source. However, the energy aspect of using biomass as a fuel also needs to be evaluated to assess the energy pros and cons of cofiring applications, considering that biomass has a lower energy density. In this study, the energy pros and cons of coal and biomass cofiring are evaluated based on the Energy Return on Energy Invested (EROEI) of the electricity generated at the CFPP. The calculation is determined based on the boundary point of use by reviewing three stages of fuel utilization: capturing, transportation, and processing. Cofiring is assumed to be implemented at an existing subcritical CFPP using direct co-combustion techniques and an energy cofiring fraction of 1–99%. The fuels used are coal with an energy density of 18,000 MJ/m³ and eight types of biomass with energy densities ranging from 1,800 to 8,000 MJ/m³. Based on the calculations, the EROEI value of electricity under coal-firing conditions is 7.86. When cofiring is implemented, the inclusion of biomass with an energy density greater than 6,000 MJ/m³ shows an increase in the EROEI value of electricity as the energy cofiring fraction increases, while the EROEI value decreases when biomass with an energy density lower than 6,000 MJ/m³ is introduced. All obtained cofiring electricity EROEI values are greater than 2 (two), indicating that cofiring is energy-productive. Variations in the specifications of heavy material handling equipment and the volumetric flow rate of the fuel do not affect the final EROEI calculation results. However, variations in CFPP efficiency affect the results by up to 3%, and variations in the truck transportation distance for biomass affect the results by up to 13%.